Hepatitis B Virus Vaccination Status and Anti Hepatitis B Surface Antibody Titer among the Health Care Workers of a Hemodialysis Unit - Shrestha, Shailendra; Roy, Pratap (Journal of Nobel Medical College, 2020)
Background: Health care workers are in high risk of getting infected with hepatitis B virus. A large proportion of them do not receive a 3-dose series of hepatitis B vaccination and have anti hepatitis B surface antibody titer <10 mIU/ml. Materials and Methods: Health care workers of the hemodialysis unit were included from March 2019 to March 2020 and were interviewed about hepatitis B vaccination status. Serum samples of the participants were analyzed for anti hepatitis B surface antibody titer. Participants with antibody titer of <10mIU/ml were given a 3-dose series of hepatitis B vaccination and antibody titer was again measured 1-2 months after the last dose. Results: Among 30 participants, 19 (63.3%) had 3-dose series of hepatitis B vaccination, and all of them had anti hepatitis B antibody titer of >10 mIU/ml. Remaining 11 participants (36.7%), with either partial (6) or no hepatitis B vaccination (5), had antibody titer of <10mIU/ml. The mean ranks of antibody titer was significantly associated with the hepatitis B vaccination status (P<0.001). All 11 participants with antibody titer of <10 mIU/ml received a 3-dose series of hepatitis B vaccine and all of them achieved antibody titer >10 mIU/ml. Conclusion: Our study shows that a large proportion of health care workers of hemodialysis unit were either partially or not vaccinated with hepatitis B vaccination and were having anti hepatitis B antibody titer of <10 mIU/ml. However, with complete 3-dose series of hepatitis B vaccination all of them achieved a protective antibody titer of ≥10 mIU/ml.